Incentivizing and nudging farmers to spread information: Experimental evidence from Ethiopia. Issue 3 (15th September 2022) - Balew, Solomon; Bulte, Erwin; Abro, Zewdu; Kassie, Menale
Abstract: Information does not flow freely through social networks. We use an experiment to study knowledge diffusion about an innovation (integrated pest management, IPM) in farmer groups in Ethiopia. Group leaders are incentivized to share knowledge with members through the conditional provision of material or social prestige rewards. We combine incentives with loss‐framed messaging to leverage loss aversion. Incentives increase diffusion effort, and combining incentives with loss‐framed messaging increases effort further. However, the treatments failed to induce follower farmers to experiment with IPM. We also document that reclaiming material rewards is difficult after a long delay, attenuating the effectiveness of the loss frame.